CONSUMPTION PATTERN OF CONVENIENCE FOODS AMONG CONSUMERS IN KANNUR DISTRICT, KERALA: CONSUMPTION PATTERN OF CONVENIENCE FOOD AMONG CONSUMERS - TEENA THOMAS; ANU JOSEPH (The Journal of Research ANGRAU, 2026)
The consumption of convenience foods has been steadily increasing in recent years, making it important to understand the factors driving this trend. The present study examines the socioeconomic factors influencing convenience food consumption patterns among consumers in Kannur district, Kerala, India. A total of 175 respondents, aged 18 to 75 years, including both males and females, representing various socio-economic strata, participated in the survey. The results of the study reveal that convenience food consumption was predominantly higher among individuals of the younger age group (35%), those residing in rural areas (33%) and people with higher educational qualifications (24%). Expenditure on convenience foods constitute less than 10% of their monthly income. The study also identifies social media advertisements and recommendations from relatives and friends as significant factors influencing the purchase of convenience foods. The frequent purchase of items such as biscuits and bread was a more common consumable among the subjects. This study revealed an increase in the consumption of ready-to-eat and ready-to-cook products in rural areas compared to other regions.